Advancing the Reference Narrative: Assessing Student Learning in Research Consultations - R. Bradley, Doreen; Oehrli, Angie; Rieh, Soo Young; Hanley, Elizabeth; Matzke, Brian S. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – As reference services continue to evolve, libraries must make evidence based decisions about their services. This study seeks to determine the value of reference services in relation to student learning acquired during research consultations, by soliciting students’ and librarians’ perceptions of consultation success and examining the degree of alignment between them.Methods – The alignment of students’ learning outcomes (reported skills and knowledge acquired) with librarians’ expectations for student learning during consultations was assessed. An online questionnaire was conducted to gather responses from students who had sought consultation services; 20 students participated. In-person interviews took place with eight librarians who had provided these consultations. The online questionnaire for students included questions about students’ assessments of their self-identified learning goals through consultation with a librarian and their success at applying the knowledge and skills gained. Librarian interviews elicited responses about students’ prior research experience, librarians’ objectives for student learning, librarians’ perceptions of student learning outcomes, and perceived consultation success. The responses of both the students and the librarians were coded, matched, and compared.Results – Students and librarians both considered the consultation process to be successful in advancing learning objectives and research skills. All students reported that the consultations met their expectations, and most reported that the skills acquired were applicable to their projects and significantly improved the quality of their work. Librarians expressed confidence that students had gained competency in the following skill sets: finding sources, search strategy development, topic exploration, specific tool use, and library organization and access. A high degree of alignment was observed in the identification by both students and librarians of “finding sources” as the skill set most in need of enhancement or assistance, while some disparity was noted in the ranking of “search strategy development,” which librarians ranked second and students ranked last.Conclusion – The data demonstrate that both students and librarians perceived individual research consultations as an effective means to meet student learning expectations. Study findings suggest that as reference models continue to change and reference desk usage declines, research consultations remain a valuable element in a library’s service model and an efficient use of human resources.